Modified two-mode fiber-based filter and its application in a switchable thulium-doped fiber laser. (July 2022) - Qin, Qi; Yan, Fengping; Liu, Yan; Guo, Ying; Li, Ting; Cheng, Dan; Yu, Chenhao; Yang, Dandan; Suo, Yuping; Zhou, Hong; Kumamoto, Kazuo; Feng, Ting
Highlights: A few-mode fiber-based polarization controller (FMF-based PC) was fabricated and characterized. The fabricated FMF-based PC was used to construct a thulium-doped fiber laser for the first time to the best of our knowledge. The maximal fluctuation of center wavelength and output power was 0.097 nm and 0.837 dB, respectively, within an observation time of sixty minutes. In addition, the output characteristics are investigated. Abstract: A few-mode fiber-based polarization controller (FMF-based PC) fabricated by coiling a two-mode fiber filter into the three plates of a single-mode fiber-based PC is proposed and characterized in this work. The output spectrum of the proposed FMF-based PC varies with the rotation angle of the three plates. By sequentially rotating the three plates, the maximum peak wavelength and extinction ratio variation is 1.399 nm and 4.371 dB, respectively. Based on the proposed FMF-based PC, a thulium-doped fiber laser (TDFL) with an optical signal-to-noise ratio of ∼ 40 dB and switchable single-wavelength output is constructed. Within the observation period of an hour, the maximum fluctuation of center wavelength and corresponding output optical power is 0.097 nm and 0.837 dB, respectively. The output performance of the TDFL regarding power scaling, slope efficiency, and threshold power is also investigated. The proposed fiber laser with compact structure and switchable output demonstrates advantages for application in optical sensors and communication systems.